3D surface imaging of the human female torso in upright to supine positions. Issue 4 (April 2015) - Reece, Gregory P.; Merchant, Fatima; Andon, Johnny; Khatam, Hamed; Ravi-Chandar, K.; Weston, June; Fingeret, Michelle C.; Lane, Chris; Duncan, Kelly; Markey, Mia K.
Highlights A 3D camera-tilt table (system) was used to image breasts at different angles. We describe the methods used to validate the imaging system. The system can determine quantitative changes in breast morphology.